Role of Nigella Sativa (Black Cumin Seeds) as an Adjunct Therapy in Treating Severe and Critical COVID -19 Infection Compared to Those with Standard Therapy: An Open Label Randomized Clinical Trial - Mohammad Omar Faruq; Amina Sultana; Umme Kulsum Chy; Karishma Shamarukh; Chowdhury Tasneem Hasin; Mohammed Salah Uddin; Samira Humaira Habib; Susmita Hossain Natasha; Tamanna Yasmin Shena; Tasmia Kashfi; et al. (Bangladesh Critical Care Journal, 2023)
Background: During recent COVID-19 pandemic (2019-2021) clinician-researchers had been looking for effective treatment of Covid-19 infection. Nigella sativa (NS), a well-known herbal medicine, has beenused asanti-viral, anti-inflammatory, immune modulatory, anti-oxidant, broncho-dilatory, anti-histaminic, anti-tussive activitiesfor patients with mild to moderate COVID-19 infection. Our study aimed to determine the efficacy of NS for treatment of severe and critically ill Covid-19 patients as an adjunct therapy with conventional treatment. Method: This wasan open label randomized clinical trial conducted in severely and critically ill COVID-19 patients admitted into COVID ICU of United Hospital, Dhaka, Bangladesh. The study subjects were randomly divided into two equal groups: NS group in which subjects received NS orally in addition to the conventional treatment, and Control group, who received conventional treatment only. Primary outcome focused mainly on duration of ICU stay, use of mechanical ventilation (MV)/noninvasive ventilation (NIV)/ High-flow nasal cannula (HFNC) oxygen (HFNO) and mortality. The secondary outcomes were based on comparison of those above mentioned parameters between the groups (NS and Control). Results: A total of 150 subjects were enrolled according to eligibility criteria.There were 60 deaths (29 NS + 31 Cont.) and 90 survivals (46 NS + 44 Cont.). Among the survivals 16 NS subjects as opposed to 6 Cont. subjects stayed in ICU for 8 to 14 days (P = 0.043). Twenty one subjects of NS group as opposed to 8 subjects of Cont. group stayed in ICU for less than 7 days to 14 days. Whereas among subjects who died there was no significant difference in length of stay among majority of NS and Cont. subjects. NS group required significantly lower number of O2 delivery methods likemechanical ventilation (MV), noninvasive ventilation (NIV),High-flow nasal oxygen (HFNO) compared to their counterparts on Day 7 and Day 14 of stay in ICU. Conclusion: NS as an adjunct therapy with severe and critical COVID 19 infection was associated with some reduction of duration of stay in ICU but significantly less requirement of invasive and non-invasive ventilator support, high flow nasal oxygen than standard treatment group. Establishing accurately therapeutic efficacy of NS in critically ill COVID-19 patients requires placebo controlled double blind studies. Bangladesh Crit Care J September 2023; 11 (2): 75-82